Discovery of dual positive allosteric modulators (PAMs) of the metabotropic glutamate 2 receptor and CysLT1 antagonists for treating migraine headache. Issue 2 (15th January 2017) - Blanco, Maria-Jesus; Benesh, Dana R.; Knobelsdorf, James A.; Khilevich, Albert; Cortez, Guillermo S.; Mokube, Fese; Aicher, Thomas D.; Groendyke, Todd M.; Marmsater, Fredrik P.; Tang, Tony P.; Johnson, Kirk W.; Clemens-Smith, Amy; et al.
Graphical abstract: Abstract: Pyridylmethylsulfonamide series were the first reported example of positive allosteric modulators (PAM) of the mGlu2 receptor. The hydroxyacetophenone scaffold is a second series of mGlu2 PAMs we have identified. This series of molecules are potent mGlu2 potentiators and possess significant CysLT1 (cysteinyl leukotriene receptor 1) antagonist activity, showing in vivo efficacy in a dural plasma protein extravasation (PPE) model of migraine. In this paper, we describe the dual SAR, pharmacokinetics and preclinical in vivo efficacy data for a tetrazole containing hydroxyacetophenone scaffold.